Deep Sequencing to Detect Diversity of Trypanosoma cruzi Infection in Patients Coinfected With Human Immunodeficiency Virus and Chagas Disease. (8th July 2021) - Bowman, Natalie M; Balasubramanian, Sujata; Gilman, Robert H; Parobek, Christian; Calderon, Maritza; Waltmann, Andreea; Messenger, Louisa A; Sanchez, Leny; Bern, Caryn; Juliano, Jonathan J; ,
Abstract: Chagas disease, caused by Trypanosoma cruzi, can reactivate and cause severe acute disease in immunocompromised patients such as those infected with human immunodeficiency virus (HIV). We conducted amplicon deep sequencing of a 327-bp fragment of the tcscd5 gene using an Ion Torrent PGM directly from clinical samples from HIV patients with high parasitemia. We describe the within-host diversity, both characterizing the discrete typing unit of the infections and confirming the presence of multistrain infections, directly from clinical samples. This method can rapidly provide information on the genetic diversity of T. cruzi infection, which can have direct impacts on clinical disease. Abstract : Amplicon deep sequencing can be used to characterize multiplicity of infection and genotype Trypanosoma cruzi infections in patient coinfected with human immunodeficiency virus.